2021
DOI: 10.3390/pr9071232
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Bullwhip Effect in Quality and Waste in Perishable Supply Chain

Abstract: The bullwhip effect results from inefficiencies in the supply chain; in perishable products, the inefficiencies are quality in the supply chain and product waste. We carried out a literature review to determine the causes of the bullwhip effect and the supply chain’s quality factors of this phenomenon’s perishable products. Update the demand, the level of deterioration of the product, and the number of intermediaries is the causes of the bullwhip effect most investigated. On the other hand, the product’s safet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 81 publications
(125 reference statements)
0
6
0
Order By: Relevance
“…In the present study, the e ect of combined use of various forecasting methods on the bullwhip e ect in a four-level supply chain, including retailers, wholesalers, manufacturers, and suppliers, is investigated. Although a similar issue has been explored in many previous research studies, considering the nature of supply chain components, it is more consistent with reality [1]. For this purpose, rst, the supply chain was simulated.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…In the present study, the e ect of combined use of various forecasting methods on the bullwhip e ect in a four-level supply chain, including retailers, wholesalers, manufacturers, and suppliers, is investigated. Although a similar issue has been explored in many previous research studies, considering the nature of supply chain components, it is more consistent with reality [1]. For this purpose, rst, the supply chain was simulated.…”
Section: Introductionmentioning
confidence: 89%
“…Also, she compared the two neural network methods with the ARIMA method and concluded that the neural network method reduces the bullwhip effect. Durán Peña et al [9] carried out a literature review to determine the causes of the bullwhip effect and the supply chain's quality factors of this phenomenon's perishable products. Updating the demand, the level of deterioration of the product, and the number of intermediaries is the causes of the bullwhip effect most investigated.…”
Section: Literature Reviewmentioning
confidence: 99%
“…(2) Demand information: Some agricultural products are challenging to store, and information asymmetry can cause the bullwhip effect. Therefore, effective demand information feedback from downstream SCs to upstream enterprises is crucial for predicting market demand, adjusting production plans, enhancing risk mitigation capabilities, and ultimately improving the operational efficiency of agricultural SCs [22].…”
Section: Establishment Of the Theoretical Modelmentioning
confidence: 99%
“…To solve the model, the NSGA-II was enhanced. Managing the SCs of perishable products has also been the subject of recent review publications (e.g., Amini et al 2020 ; Awad et al 2020 ; Durán Peña et al 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%